The Performance of Active Coated Nanoparticles Based on Quantum-Dot Gain Media. (20th September 2012) - Campbell, Sawyer D.; Ziolkowski, Richard W.
Abstract : Quantum-dots (QDs) provide an exciting option for the gain media incorporated in active coated nanoparticles (CNPs) because they possess large gain coefficients resulting from their extreme confinement effects. The optical properties of core/shell QDs can be tuned by changing the relative size of the core/shell, that is, by effectively changing its band gap structure. Similarly, the resonance of a CNP can be adjusted by changing the relative sizes of its layers. It is demonstrated here that by optimally locating the QDs inside a resonant CNP structure it is possible to greatly enhance the intrinsic amplifying behavior of the combined QD-CNP system.